Vegetation Index Assessment Modeling Using Remote Sensing And Soil Surveying The Slope of Argopura Mountain: a Case Study in Kalianan Village, Krucil District, Probolinggo Regency - Basuki, Basuki; Prasetya, Eka Bagus Budi; Mashughestiningrum, Anggelya; Pitaloka, Amelia Ayu; Hia, Jarni Devita Faomasi; Fitriani Sadim Klaida (University of Jember, 2024)
Vegetation is a form of soil with a density level in each region that is influenced by other land factors such as rainfall, soil conditions, and water. Density levels can be analyzed either manually in the field or using remote sensing technology. Field observations have weaknesses, one of which is that the time used for a wide area > 1 ha requires > 2 days. The use of remote sensing technology has the advantage of being able to cover large areas in a short time with a modeling system. The research uses a data exploration modeling method with an NDVI approach to calculate the analysis of Landsat 8 image bands. NDVI is calculated based on bands 4 (red) and 5 (near-Infrared). The research results show that in 2017, Kalianan Village, Krucil District, had a vegetation index dominated by dense and very dense density classes. In 2022, the vegetation index of Krucil Village will be dominated by medium- and low-density classes. The differences that occur in 2017 and 2022 could occur due to the deforestation of land for tourism and residential areas.